Media sosial sebagai platform cyberbullying di masa pembelajaran jarak jauh - Tri Widayanti; Bety Agustina Rahayu; Sutono Sutono (Health Sciences and Pharmacy Journal, 2022)
Distance learning activities programmed by the government due to the Covid-19 pandemic have made students spend more time in front of technology devices and the internet. Social media is one of the platforms commonly used to support distance learning programs. It is not only used to communicate between students, but also used as learning media and discussing through groups or classes on social media. This makes students more accustomed and even their daily life cannot be separated from social media. One of the negative impacts that arise is the phenomenon of cyberbullying. The more time spent on social media, the more likely students are to become cyberbullies. This research is to find out the types of social media that are often used and the forms of cyberbullying behavior by students in SMA Y. The method used was a case study on students of SMA Y on class X and XI. The sample used purposive sampling and questionnaire was used as instrument to collect the data. The technique of collecting and presenting data used descriptive statistics. The results of the study were 36 students (97.3%) never bullied on Instagram, 1 student (2.7%) often bullied on Instagram, 29 students (78.4%) never bullied on whatsApp, 6 students (16.2%) sometimes bully on whatsapp, 2 students (5.4%) often bully on whatsapp, 36 students (97.3%) never bully on facebook, and 1 student (2.7 %) often did bullying on facebook. WhatsApp social media was the most frequently used by students in carrying out cyberbullying actions with the most form being flaming behavior